2019
DOI: 10.3389/fmicb.2019.00750
|View full text |Cite
|
Sign up to set email alerts
|

The Zn(II)2Cys6-Type Transcription Factor ADA-6 Regulates Conidiation, Sexual Development, and Oxidative Stress Response in Neurospora crassa

Abstract: Conidiation and sexual development are critical for reproduction, dispersal and better-adapted survival in many filamentous fungi. The Neurospora crassa gene ada-6 encodes a Zn(II)2Cys6-type transcription factor, whose deletion resulted in reduced conidial production and female sterility. In this study, we confirmed the positive contribution of ada-6 to conidiation and sexual development by detailed phenotypic characterization of its deletion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 42 publications
1
32
0
Order By: Relevance
“…We also note that in [63], authors show that Tr -MedA is repressed by CRE-1 in QM9414 ∆cre1, thus suggesting a role of the partial carbon catabolite derepression regarding the observed down-regulation of ID 123713. In N. crassa, acon-3 is positively regulated by the transcription factor ADA-6 involved in conidiation, sexual developement, and oxidative stress response [60]. Interestingly, ypr1 (ID 102499), the yellow pigment regulator, DE in our data, displayed 35 % identity with ada-6 .…”
Section: Discussionmentioning
confidence: 57%
“…We also note that in [63], authors show that Tr -MedA is repressed by CRE-1 in QM9414 ∆cre1, thus suggesting a role of the partial carbon catabolite derepression regarding the observed down-regulation of ID 123713. In N. crassa, acon-3 is positively regulated by the transcription factor ADA-6 involved in conidiation, sexual developement, and oxidative stress response [60]. Interestingly, ypr1 (ID 102499), the yellow pigment regulator, DE in our data, displayed 35 % identity with ada-6 .…”
Section: Discussionmentioning
confidence: 57%
“…We determined that the N. crassa ortholog of MedA is acon-3 , a gene required for early conidiophore development and female fertility. In N. crassa , acon-3 is positively regulated by the transcription factor ADA-6 involved in conidiation, sexual developement, and oxidative stress response [58]. Interestingly, ypr1 (ID 102499), the yellow pigment regulator, DE in our data, displayed 35% identity with ada-6 .…”
Section: Discussionmentioning
confidence: 72%
“…Cluster , whose median profile exhibits a slight repression across lactose concentrations encompasses transcription factors whose ortholog are involved in the development: Tr –WET-1 (ID 4430, [55]), Tr –PRO1 (ID 76590, [56, 57]) and Tr –ACON-3 (ID 123713, [58]). We recall that the Tr –XXX notation refers to the gene in T. reesei for which the ortholog in an other specie is XXX (see the Functional analysis section in Materials and Methods).…”
Section: Resultsmentioning
confidence: 99%
“…We detected the expression of more than 70 genes which were reported in fruiting body development in N. crassa by qRT-PCR (Kim and Nelson, 2005;Sun et al, 2012Sun et al, , 2019Garud, 2013;Chinnici et al, 2014;Lehr et al, 2014;, and found that poi-2, an essential gene for female fertility in N. crassa, had a dramatic response to cpc-2 deletion (more than 100-fold change) after fruiting induction in N. crassa (Figure 5), indicating that CPC-2 regulates transcription of poi-2. To see whether FvCPC2 can functionally replace the role of CPC-2 in transcriptional regulation, transcript levels of poi-2 were analyzed by qPCR in wild type, the cpc-2 strain, the cpc-2; cpc-2 strain and the Fvcpc2; cpc-2 strain.…”
Section: Fvcpc2 Can Functionally Replace the Role Of N Crassa Cpc-2 mentioning
confidence: 96%